Effect of Garcinia kola on Atorvastatin Dissolution Profile: An Indication for Possible Drug-Drug Interactions After Oral Administration (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Herb-drug interactions are of growing concern due to the widespread use of herbal supplements alongside medications. These interactions can affect therapeutic outcomes. Understanding and identifying specific interactions is crucial for ensuring safe and effective medication use.Objective: This study investigated the impact of Garcinia kola, a common food supplement, on the dissolution of atorvastatin tablets.Methods: The dissolution profiles of atorvastatin tablets were investigated alone and in the presence of varying concentrations of G. Kola by mixing 1, 2, or 4g of G. Kola powder respectively with the dissolution medium. Samplings were performed at predetermined time points (10, 20, 30, 45 and 60 minutes) and the amount of atorvastatin dissolved was measured using a validated HPLC method. Statistical analyses were conducted to assess the significance of the observed differences.Results: The percentages of atorvastatin released in dissolution medium without G. kola were 31.38±11.81, 46.02±8.73, 72.23±33.30, 63.55±27.10, 82.54±31.12% across the sampling time points. Whereas the percentage of drug released were 17.01±7.33, 27.02±8.42, 34.70±13.90, 39.74±13.53, 28.47±11.78% in the presence of 1g G. kola; 12.44±5.89, 11.87±1.51, 23.33±5.18, 27.33±8.50, 52.49±11.66% in the presence of 2g G. kola and 2.28±3.53, 4.94±7.21, 7.26±9.01, 4.68±7.37, 6.86±8.70% in the presence of 4g G. kola. There was a statistically significant difference in the amount of drug dissolved in conditions studied.Conclusion: There was a significant change in the dissolution profile of atorvastatin with increasing concentrations of G. kola. This suggests a need to establish the impact of G. kola on the disposition of atorvastatin in vivo.
Keywords: Garcinia kola; Atorvastatin; Drug-drug interactions